Atividade inibitória da molécula de Quorum Sensing Farnesol frente à cepas de Trichosporon asahii e T. inkin - Pereira, Lívia Maria Galdino (2018)
The genus Trichosporon corresponds to the fungi belonging to phylum Basidiomycota, usually associated to superficial infections like piedra branca. In recent years, this genus has been highlighted as important pathogens in systemic infections, especially in patients with immunological imbalance. Infections with Trichosporon spp. are generally associated with biofilms formation in invasive medical devices. Biofilms are communities of microbial cells surrounded by an exopolymeric matrix that exhibit increased virulence factor production, in addition to the increased tolerance phenotype to antifungals. The present study evaluated the inhibitory effect of farnesol, a molecule belonging to Candida albicans quorum sensing system, in planktonic growth and biofilm of T. asahii (n = 3) and T. inkin (n = 7). The action of farnesol in planktonic and biofilm growth protease production was also analyzed, as well as the morphological conversion of blastoconide to hyphae. The plankton cell sensitivity assay was performed by the broth microdilution method in RPMI medium of T. asahii (n = 3) and T. inkin (n = 7) at farnesol concentrations ranging from 2.33 to 1196.1 μM. Farnesol was tested as a biofilm inhibitor at concentrations between 37.37 and 1196.1 μM in adhesion, maturation and mature biofilm times. The biofilms of T. asahii (n = 3) and T. inkin (n = 7) were formed in RPMI medium with inoculum of 106 cells / mL and incubated at 35 °C under shaking at 80 rpm and then analyzed for biomass, metabolic activity and ultrastructure by laser confocal microscopy and scanning electron microscopy. Filamentation inhibition was analyzed by microculture on malt agar containing compound concentrations of 598 μM and 1196.1 μM. It was observed that farnesol inhibited planktonic growth by 80% at the concentration of 598 μM concentration against T. asahii and for T. inkin reduced by 80% in the range of 74.75 to 598 μM for T. inkin and in the development of the biofilm at the concentration of 149.5 μM for both strains, altering its structure. The farnesol in contact with the mature biofilm reduced T. asahii biofilm at 568.1 μM and of T. inkin at 299 μM concentrations by 50%. Farnesol inhibited gradual filamentation at 598 and 1196.1 μM concentrations, with blastoconidia predominance. The scanning electron microscopy in biofilm analysis were observed that farnesol was able to inhibit cell adhesion and hyphae development, as well as interfered negatively in the biofilm maturation, modifying the hyphae morphologies. The contact between farnesol and mature biofilm disorganized biofilm robustness, destroying the extracellular matrix and water channels. Thus, it is necessary to investigate the mechanisms of farnesol compound acts on the Trichosporon spp. cells and its potential use as an alternative for tricosporonosis prophylaxis.